Temporal, Spatial, and Genomic Analyses of Enterobacteriaceae Clinical Antimicrobial Resistance in Companion Animals Reveals Phenotypes and Genotypes of One Health Concern - Singleton, David A.; Pongchaikul, Pisut; Smith, Shirley; Bengtsson, Rebecca J.; Baker, Kate; Timofte, Dorina; Steen, Stephen; Jones, Matthew; Roberts, Larry; Sánchez-Vizcaíno, Fernando; Dawson, Susan; Noble, P.-J. M.; et al. (Frontiers in Microbiology, 2021)
Background Antimicrobial resistance (AMR) is a globally important one health threat. The impact of resistant infections on companion animals, and the potential public health implications of such infections, has not been widely explored, largely due to an absence of structured population-level data. Objectives We aimed to efficiently capture and repurpose antimicrobial susceptibility test (AST) results data from several veterinary diagnostic laboratories (VDLs) across the UK to facilitate national companion animal clinical AMR surveillance. We also sought to harness and genotypically characterise isolates of potential AMR importance from these laboratories. Methods We summarised AST results for 29,330 canine and 8,279 feline Enterobacteriaceae isolates originating from companion animal clinical practice, performed between April 2016 and July 2018 from four VDLs, with submissions from 2,237 UK veterinary practice sites. Results Escherichia coli (E. coli) was the most commonly isolated Enterobacteriaceae in dogs (69.4% of AST results, 95% confidence interval, CI, 68.7-70.0) and cats (90.5%, CI 89.8-91.3). Multi-drug resistance was reported in 14.1% (CI 13.5-14.8) of canine and 12.0% (CI 11.1-12.9) of feline E. coli isolates. Referral practices were associated with increased E. coli 3rd generation≤ cephalosporin resistance odds (dogs: odds ratio 2.0, CI 1.2-3.4). We selected 95 E. coli isolates for whole genome analyses, of which seven belonged to sequence type 131, also carrying the plasmid-associated extended spectrum β-lactamase gene blaCTX-M-15. The plasmid-mediated colistin resistance gene mcr-9 was also identified for the first time in companion animals. Conclusions Linking clinical AMR data with genotypic characterisation represents an efficient means of identifying important resistance trends in companion animals on a national scale.